Regulation of insulin-like growth factor (IGF)-I action by matrix metalloproteinase-3 involves selective disruption of IGF-I/IGF-binding protein-3 complexes. - Fowlkes, J; Serra, D; Bunn, R; Thrailkill, K; Enghild, J; Nagase, H (2004)
IGF-I and IGF-II play important roles in growth and development via interactions with cell-surface receptors; however, in nature, IGFs are sequestered by at least six soluble, high-affinity IGF-binding proteins (IGFBPs), namely IGFBPs 1-6. Herein, we demonstrate that the stromal cell-derived extracellular matrix-degrading metalloproteinase stromelysin 1 (matrix metalloproteinase 3) disrupts IGF/IGFBP-3 complexes and liberates free, intact IGFs, leading to phosphorylation of cell surface type 1 IGF receptors and cellular proliferation. Tissue inhibitor of metalloproteinases (TIMP-1) or an antibody to the type 1 IGF receptor mitigates IGF-mediated cellular proliferation. Thus, these studies suggest that matrix metalloproteinases, beyond their effects on extracellular matrix turnover, regulate cellular proliferation by modulating the bioavailability of IGFs, an event critical for such diverse phenomena as embryo development, morphogenesis, angiogenesis, and tumorigenesis.